Neurosciences in Buddhist India - Arushi Kumar; Raj Kumar (Indian Journal of Neurosurgery)
Neurosciences in Buddhist era was mainly based on power of mind and thoughts. It emphasized mainly about the power of mind, control of thoughts, purification, and modifications of erroneous thought process, which should result in truthful and correct practices and subsequent actions by human beings to remain happy. Buddhism believes that most diseases of human body are secondary to mind and that these can be healed by controlling the erroneous thoughts and practices of Dhamma. Though the treatment for neurologic disorders such as headache, stress, and anxiety was primitive, it was mainly based on purification of mind and righteous pathway of Dhamma followed by medicines, modification in dietary and other living habits, etc. Enough evidence (including operated case-based commentary) shows that cranial surgery was also performed following appropriate diagnosis. The concept of diagnosis, preoperative evaluation, explanation to the patient, operative procedure, perioperative care, and follow-up was also present in that era.